İpotekli konut finansmanı sistemi ve tüketicinin korunması - Can, Bilal (My University, 2013)
potekli Konut Finansmanı, Tüketicinin Korunması ÖZET İPOTEKLİ KONUT FİNANSMANI SİSTEMİ VE TÜKETİCİNİN KORUNMASI Konut finansmanı sistemlerinden nitelik ve etkinlik yönünden en önemli olan ipotekli konut finansmanı sistemi temelde tüketici işlemine dayanmaktadır. Tüketicinin korunmasını gerekli kılan sebepler, ipotekli konut kredilerinde daha da ön plana çıkmaktadırlar. Bu nedenle de tüketicinin sözleşme kurulması öncesinden sözleşmenin sona ermesine kadar her aşamada korunmasına yönelik hukuki düzenlemeler yapılmıştır. Bu düzenlemeler bazı durumlarda tüketicinin korunmasına yönelik diğer düzenlemelerden farklılık göstermektedir. Bu durum ipotekli konut kredilerinin niteliklerinden kaynaklanmaktadır. Böylelikle bu kredilerin tüketicinin korunması yönünden ayrı bir kanunu gerekli kıldığı söylenebilir. Name and Surname: Bilal Can Field: Business Administration Programme: Real Estate Valuation and Financing Supervisor: Asst. Prof. Recep Öktem Degree Awarded and Date: Master, Mart 2013 Mortgage, Protection of The Consumer

THE MORTGAGE BASED REAL ESTATE FINANCING SYSTEM AND PROTECTION OF THE CONSUMER The mortgage based real estate financing system, which is the most important in term of qualify and activity in housing financing system, is based on consumer transaction. The reasons which demand protection of the consumers are being come into prominence more in mortgage loans. So that, legislations have been made for protection of the consumers at every stage of contract, before establishment to the end. These legislations differ from other legislations which are for protection of the consumers in some cases. This originates from qualify of mortgage loans. Thus it can be said that mortgage loans demand a particular act for protection of the consumers.
Keywords: Konut Kredisi; Tüketicinin Korunması